Training workshop report: Climate-smart aquaculture, climate information services and gender training for the Aquaculture Bundle - Lundeba, Mary; Kanyembo, Henry; Sichone, Mercy; Kakwasha, Keagan; Mudege, Netsayi (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Aquatic food systems in Zambia and other African countries are vulnerable to climate change, calling for climate-smart approaches combining adaptation and mitigation. For example, climate smart approaches such as Integrated Agriculture Aquaculture Systems (IAAS) enhance sustainable aquaculture-agriculture production and food security in the face of climate change. IAAS combined with climate information services (CIS) delivery can help promote the resilience of aquatic and agrifood systems and the communities that depend on them. This report summarizes the proceedings of a training workshop on climate smart aquaculture implemented in the Northern Province. See annex 1 for the training agenda. WorldFish trained 37 participants, 25 men and 12 women of which 7 are youth in a training of trainers’ workshop (ToT). The participants included our bundle partners Toda Raba (Joseph Mukuka) and Aqua360 (Manfred Bwalya) and other SMEs along the aquaculture and small livestock value chain, lead fish farmers, and government officers mainly extension officers from the Department of Fisheries, agriculture camp officers, veterinary officers, meteorological officers and a representative from the National Agriculture Information Services (NAIS). Participants were trained on climate-smart aquaculture (CSA), climate information systems (CIS) and gender equity and social inclusion (GESI).